2020
DOI: 10.1186/s12884-020-02875-2
|View full text |Cite
|
Sign up to set email alerts
|

Age effect on in vitro fertilization pregnancy mediated by anti-Mullerian hormone (AMH) and modified by follicle stimulating hormone (FSH)

Abstract: Background: Both follicle stimulating hormone (FSH) and anti-mullerian hormone (AMH) are widely used to assess the ovarian reserve in women for in vitro fertilization (IVF). However, studies also showed that both AMH and FSH are significantly associated with age: as age increases, AMH decreases and FSH increases. This study aims to investigate the mechanism of age effect on IVF live birth rate, particularly through mediation and interaction by AMH and FSH. Methods: We conducted a retrospective cohort study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…For the proposed PMORN, the feature of AFC (NMIV = 1.0), E 2 level on the HCG day (NMIV = 0.951), age (NMIV = −0.354), and AMH (NMIV = 0.314) have significant NMIV, meaning that they are the dominant features affecting the ovarian response, which is in accordance with the findings in [ 13 , 27 ]. The AFC has the most significant NMIV as compared to the other features, which matches with the findings in the early work [ 12 , 28 , 29 , 30 ] that (1) the AFC is highly correlated with the number of recruited follicles and the retrieved oocytes, and (2) the AFC is regarded as the best univariate predictor of ovarian reserve and determines the number of follicles that grows in response to Gn stimulation [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For the proposed PMORN, the feature of AFC (NMIV = 1.0), E 2 level on the HCG day (NMIV = 0.951), age (NMIV = −0.354), and AMH (NMIV = 0.314) have significant NMIV, meaning that they are the dominant features affecting the ovarian response, which is in accordance with the findings in [ 13 , 27 ]. The AFC has the most significant NMIV as compared to the other features, which matches with the findings in the early work [ 12 , 28 , 29 , 30 ] that (1) the AFC is highly correlated with the number of recruited follicles and the retrieved oocytes, and (2) the AFC is regarded as the best univariate predictor of ovarian reserve and determines the number of follicles that grows in response to Gn stimulation [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
“…Results in our work suggest that we might need to re-evaluate the priority of the AMH and AFC on affecting the number of oocytes retrieved. In addition, we also find that the therapeutic regimen, days of Gn, dosage of Gn, bFSH, and infertility type have obvious influence on the ovarian response, as revealed in [ 27 , 34 ]. Regarding the infertility duration and infertility cause, their NMIV value is very small (−0.039 and 0.07), meaning they have very little effect on the COS outcome.…”
Section: Discussionmentioning
confidence: 93%
“…Multinomial regression revealed an association between female age and diagnosis of female infertility [26]. For female IVF patients, follicle stimulating hormone (FSH) and anti-mu□llerian hormone (AMH) are the two most frequently utilized ovarian reserve tests that serve as important markers related to successful IVF outcomes [27]. It is suggested that AMH >0.8-1.0 ng/ml is indicative of normal ovarian reserve, while FSH >10 mIU/ml is indicative of diminished ovarian reserve [28].…”
Section: Discussionmentioning
confidence: 99%
“…-mu llerian hormone (AMH) are the two most frequently utilized ovarian reserve tests that serve as important markers related to successful IVF outcomes [27]. It is suggested that AMH >0.8-1.0 ng/ml is indicative of normal ovarian reserve, while FSH >10 mIU/ml is indicative of diminished ovarian reserve [28].…”
Section: Discussionmentioning
confidence: 99%